ANALISIS KUALITAS SOAL UJIAN AKHIR SEMESTER MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II SD BERDASARKAN TAKSONOMI BLOOM - Fitri Muwahhida, Muziya Ananda; Sholehuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the quality of the Even Semester Final Examination questions for Civics Education (Pendidikan Pancasila) subject for Grade II Elementary School at SD Plus Muhammadiyah Kota Sungai Penuh, Jambi, Academic Year 2025/2026. The research used descriptive qualitative method with document analysis approach. The object of analysis consisted of 40 multiple-choice items covering two main themes: diversity of identity and environmental cleanliness. The analysis focused on three dimensions: (1) cognitive level based on Bloom's Taxonomy revised by Anderson and Krathwohl, (2) alignment between test items and learning objectives (content validity), and (3) item construction quality. The findings revealed that 87.5% of items were classified at the C1 (Remember) level and 12.5% at the C2 (Understand) level, with no items reaching higher-order thinking skills (HOTS) at C3–C6 levels. Content validity analysis indicated that the items were generally relevant to the Grade II Pancasila Education curriculum, although the distribution of cognitive levels was unbalanced. Several items also showed weaknesses in terms of item construction, particularly in formulating distractors. This study recommends that educators improve the quality of assessments by developing questions that encompass higher cognitive levels to support better critical thinking skills in elementary school students.